Effects of reproductive stage and temperature on rates of oxygen consumption in Paralithodes platypus (Decapoda: Anomura) - Romero, Maria Carolina; Tapella, Federico; Stevens, Bradley; Loren Buck, C. (Journal of Crustacean Biology)
Paralithodes platypus is a large decapod that inhabits Alaskan and North Pacific waters. Females exhibit a biennial spawning cycle, requiring two years for production of fully mature oöcytes. We used respirometry and video recording to determine: 1) metabolic rates of brooding and post-brooding females, embryos, and larvae at different temperatures, 2) if females exhibit active brood care, 3) oxygen availability within the clutch, and 4) the timing of larval hatching. The rates of oxygen consumption (MO2) of brooding females was significantly higher than that of post-brooding females at night, but was similar during the day and increased significantly with temperature. MO2 of crab embryos did not differ with position in the clutch, whereas MO2 of zoeae averaged 4-fold higher than that of embryos. Larvae from the periphery of the embryo mass, either top or bottom, hatched prior to larvae from the middle of the clutch. Oxygen availability in the embryo mass varied significantly with position in the clutch; saturation was highest at the top (~ 91%), and lowest at the middle (~ 66%). Flapping of the pleon in brooding females was coincident with sudden increases in oxygen availability at the bottom of the embryo mass. The percentage of time that brooding females were engaged in flapping of the pleon was 30% higher at night than during the day. Our results address the cost of brooding in a lithodid crab and the effects of temperature on this behavior. The importance of pleonal flapping to ventilation of the embryo mass and alternative hatching mechanisms is discussed. Fil: Romero, Maria Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Kodiak Fishery Research Center. Alaska Fisheries Science Center. National Marine Fisheries Service; Estados Unidos Fil: Tapella, Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Kodiak Fishery Research Center. Alaska Fisheries ...